ASSESSMENT AND DOCUMENTATION OF FOREIGN ECONOMIC TRANSACTIONS IN TERMS OF RISK (International Journal of Innovative Technologies in Economy, 2021)
Identification, documenting and reliable assessment of risks of an enterprise foreign economic activity is a prerequisite for effective and stable operation of a business entity. The need to reflect the consequences of risks of foreign economic activity and measures undertaken to minimize them in order to avoid losses and negative results from foreign economic transactions necessitated the development of a risk-oriented accounting system of foreign economic activity of an entity. The article presents the main components of a risk-oriented accounting system. With the purpose of forming a proper documentation of foreign economic transactions in terms of risk, the forms of primary and consolidated documents are proposed. The usage of the devised forms of primary documents provides the formation of the essential informational basis to assess their impact on the performance of the enterprise. In order to reflect properly the consequences of risks and measures taken to minimize them, the main methods of assessing the risks of foreign economic activity are identified and methodological support for quantitative assessment of foreign trade risks is proposed, taking into account the probability of their occurrence and impact on foreign trade performance.